2023
DOI: 10.1021/acsomega.3c01955
|View full text |Cite
|
Sign up to set email alerts
|

Zhuyu Pill Alleviates Nonalcoholic Fatty Liver Disease by Regulating Bile Acid Metabolism through the Gut–Liver Axis

Abstract: Aim. The prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing worldwide, but there are currently limited treatment options available. Therefore, it is necessary to research new treatment strategies. Zhuyu Pill (ZYP) is a well-known herbal recipe consisting of Huanglian (Coptidis rhizoma) and Wuzhuyu (Evodiae Fructus) that has been clinically used to treat NAFLD. This study aimed to investigate the impact of ZYP on NAFLD induced by a high-fat diet (HFD) and to identify its potential mechanism. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The anti-inflammatory, lipid-lowering, and anti-cholestatic effects of CF have been reported in many papers (Wang et al, 2019;Hu et al, 2022;Lan et al, 2022), and our previous studies have confirmed that the combination of CF and TR in the treatment of cholestasis is associated with regulating the expression of genes related to lipid metabolism (Han et al, 2023a). The effect of the combination of CF and TR in the regulation of disorders of lipid metabolism has also been demonstrated by other scholars in their studies (Zhang et al, 2022;Xu et al, 2023). Amino acid metabolism is closely related to oxidative stress, e.g., tryptophan is a necessary substrate for melatonin synthesis, while melatonin has a significant anti-oxidative stress effect for treating cholestasis (Yu et al, 2018).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The anti-inflammatory, lipid-lowering, and anti-cholestatic effects of CF have been reported in many papers (Wang et al, 2019;Hu et al, 2022;Lan et al, 2022), and our previous studies have confirmed that the combination of CF and TR in the treatment of cholestasis is associated with regulating the expression of genes related to lipid metabolism (Han et al, 2023a). The effect of the combination of CF and TR in the regulation of disorders of lipid metabolism has also been demonstrated by other scholars in their studies (Zhang et al, 2022;Xu et al, 2023). Amino acid metabolism is closely related to oxidative stress, e.g., tryptophan is a necessary substrate for melatonin synthesis, while melatonin has a significant anti-oxidative stress effect for treating cholestasis (Yu et al, 2018).…”
Section: Discussionsupporting
confidence: 72%
“…For example, the Huanglian Jiedu decoction, a combination of CF with Cortex phellodendri chinensis, Radix scutellariae, and Fructus gardeniae in a 3:2:2:3 ratio, showed antipyretic effects by disrupting the JAK2/ STAT3 and MAPK signaling pathways (Lu et al, 2020a;Li et al, 2021). Similarly, the Zhuyu pill, a combination of CF with Tetradium ruticarpum (A. Jussieu) T. G. Hartley (TR) in a 1:1 ratio, exhibited a significant hypolipidemic effect through the gut-liver axis and the NF-κB signaling pathway (Pan et al, 2023;Xu et al, 2023). Although CF has shown therapeutic efficacy in various diseases, further investigations are required to explore the impact of different dosages of CF or combinations with other agents on its effectiveness.…”
Section: Introductionmentioning
confidence: 99%